MENELISIK MOTIVASI KEHIDUPAN BERASRAMA DALAM MEMBENTUK KARAKTER MAHASISWI DI ASRAMA ST. THERESA AVILA SEBAGAI CALON KATEKIS STIPAS KEUSKUPAN AGUNG KUPANG - Bria, Bonefantura Jemy; Lundut, Adriani Putri Sundari; Taek, Emilia Dolorosa (STIPAS Keuskupan Agung Kupang, 2023)
This research aims to determine the motivation for boarding life and its impact on character formation of boarding children at STIPAS Kupang Archdiocese. This research uses qualitative methods with an empirical-rational approach, prioritizing content analysis of data from observations and interviews. The results show that dormitory life provides easier access to campus, opportunities for independent study, involvement in extracurricular activities, and supportive academic facilities. Despite the presence of inhibiting factors such as conflict between residents, academic stress, and lack of staff support, concrete steps have been identified to address these challenges, including education, mediation mechanisms, and increased staff support. Thus, the life of female students in the St. Theresia Avila STIPAS Kupang Archdiocese can be an important contributor in forming the character of female students as prospective catechists, by providing opportunities for the development of skills and values that are important in pastoral ministry.